The effect of pedestrian roads in providing a comfortable environment for humans - حسن, د.سوزان عبد (Journal of Planner and Development, 2010)
Planning of cities show great attention on streets planning as one of the most structural component foundations for cities, that providing many functional needs and connect parts of the city each other, and work as a commercial and services activities centers. Instead of this highly focused on distributing streets with different streets types such as economical and trading and housing streets. This concerned was only on the dimensions and scales of different types of vehicles and their movement. When scale and dimension and movement of mans were as a second priority in designing and planning streets. Which came's first for traditional streets. The research try to submit some designs guides for planners that contribute in re concerning the human environment through studying the most effective needs such as psychological and environmental and acoustical. That achieving comfort environment for walking person inside streets